Comparison of 2% Lignocaine with 1:200,000 Adrenaline and Mixture of 2% Lignocaine with 1:200,000 Adrenaline and 0.5% Bupivacaine as peribulbar Anaesthesia - Shah, Ashfaq Ali; Samar, Bakht; Nawaz, Abid; Muhammad, Shad (Journal of Postgraduate Medical Institute, 2011)
Local anaesthesia is the preferred method of anaesthesia for many ocular surgical procedure. Soon after the discovery of local anaesthesia, opthlmology was the first field to appreciate is clinical implications. Knapp introduced retrobulbar anaesthesia in 1884. However the much safer peribulbar anaesthesia has largely replaced the retrobulbar anaesthesia.